1997
DOI: 10.1289/ehp.97105s61445
|View full text |Cite
|
Sign up to set email alerts
|

Ultramorphological sperm characteristics in the risk assessment of health effects after radiation exposure among salvage workers in Chernobyl.

Abstract: We present a pilot study of individuals (liquidators) who were engaged in clean-up operations after the disaster at the nuclear power plant at Chernobyl in Ukraine. In the 10 years since the disaster, adverse health effects among exposed individuals have not been clearly defined. There is widespread fear of damage to the reproductive system, with implications for fertility problems and adverse effects on offspring. Bearing this in mind, methods to evaluate the potential for production of fertile semen have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…A high proportion of morphologically abnormal spermatozoa in the exposed group, therefore indicates the possible association between chronic radiation exposure and defective spermiogenesis. Our observations are in agreement with the results from an earlier study which demonstrated increased sperm ultra-structural defects in Chernobyl salvage workers exposed to radiation [17]. Apart from morphological abnormalities, the exposed subjects in the present study also had an increased incidence of sperm head vacuoles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A high proportion of morphologically abnormal spermatozoa in the exposed group, therefore indicates the possible association between chronic radiation exposure and defective spermiogenesis. Our observations are in agreement with the results from an earlier study which demonstrated increased sperm ultra-structural defects in Chernobyl salvage workers exposed to radiation [17]. Apart from morphological abnormalities, the exposed subjects in the present study also had an increased incidence of sperm head vacuoles.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in sperm methylation pattern, induced by toxic exposure, may have widespread repercussions on chromatin integrity and gene expression [16]. Hence, there is a risk of damage to the reproductive system from occupational radiation exposure with adverse implications for fertility and reproductive outcome [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in cleanup workers exposed to radiation from the Chernobyl nuclear power plant accident in 1986 showed alterations in human semen quality (Fischbein et al 1997). Interestingly, an elevated frequency of chromosome aberrations was observed in the offspring of fathers exposed to low doses of radiation during the cleanup of the nuclear plant (Aghajanyan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies in human and animal populations exposed to radiation from the Chernobyl nuclear power plant accident in 1986 showed DNA damage in sperm and an overall increase in generation of reactive oxygen metabolites [84, 85]. Further analyses in the offspring of fathers exposed to low doses of radiation during cleanup of the nuclear plant showed an elevated frequency of chromosome aberrations, which may lead to increased morbidity over their lifetimes [86].…”
Section: Do Paternal Exposures To Low Dose Ionizing Radiation Promotementioning
confidence: 99%